Opportunities and limitations of bone replacement materials: A case report Möglichkeiten und grenzen von knochenersatzmaterialien ein fallbericht - Döring, Hendrik; Schmitt, Christian Martin; Lutz, Rainer; Prechtl, Christopher; Schlegel, Karl Andreas (Implantologie, 2012)
Sufficient bone in both the vertical and horizontal dimensions is a prerequisite for successful implant therapy. Over the course of the recent development of modern dentistry, different ways and techniques to create adequate bone levels have been developed. In particular, focus is placed on bone replacement materials that promise to eliminate donor site morbidity and quantitative limitations. The following is an overview of existing bone replacement materials in which their clinical use and limits of applicability are highlighted. In addition, a clinical case is presented to emphasize the remarks of bone substitute materials.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Bone substitute material; Implantation; Infection; Osteomyelitis; Vertical augmentation